Laparoscopic esophagomyotomy for achalasia in children: A review - Pandian, T Kumar (World J Gastrointest Endosc, 2016)
Esophageal achalasia in children is rare but ultimately requires endoscopic or surgical treatment. Historically, Heller esophagomyotomy has been recommended as the treatment of choice. The refinement of minimally invasive techniques has shifted the trend of treatment toward laparoscopic Heller myotomy (LHM) in adults and children with achalasia. A review of the available literature on LHM performed in patients < 18 years of age was conducted. The pediatric LHM experience is limited to one multi-institutional and several single-institutional retrospective studies. Available data suggest that LHM is safe and effective. There is a paucity of evidence on the need for and superiority of concurrent antireflux procedures. In addition, a more complete portrayal of complications and long-term (> 5 years) outcomes is needed. Due to the infrequency of achalasia in children, these characteristics are unlikely to be defined without collaboration between multiple pediatric surgery centers. The introduction of peroral endoscopic myotomy and single-incision techniques, continue the trend of innovative approaches that may eventually become the standard of care.